Broadband ultrafast nonlinear optical studies revealing exciting multi-photon absorption coefficients in phase pure zero-dimensional Cs4PbBr6 perovskite films. Issue 3 (20th December 2018) - Krishnakanth, K. N.; Seth, Sudipta; Samanta, Anunay; Venugopal Rao, S.
Abstract : Lead halide perovskite nanocrystals have recently demonstrated promising nonlinear optical properties such as strong two-photon absorption, three-photon absorption, four-photon absorption and their respective cross-sections. Abstract : Lead halide perovskite nanocrystals (NCs) apart from their overwhelming optoelectronic applications have recently demonstrated promising nonlinear optical (NLO) properties such as strong two-photon absorption cross-sections (∼10 5 GM), two-photon fluorescence, and saturable absorption even at very high peak intensity. Zero-dimensional perovskite-related materials (0-D PRMs) are a new class of materials offering a high exciton binding energy ( E g ≥ 180 meV) with a strong photoluminescence (PL) quantum yield in few cases. Herein, we report the broadband third-order NLO properties of phase pure Cs4 PbBr6 0-D PRM achieved using the Z -scan and degenerate four-wave mixing techniques in the femtosecond regime. Considering the growing content of the fluorescent and non-fluorescent forms of this material, we have performed our studies on both of them. These perovskite NCs exhibited strong multi-photon absorption properties in the near-infrared region with two-photon absorption (2PA) (cross-section, σ 2 = 10 −43 –10 −44 cm 4 s equivalent to ∼10 6 GM) in the 500–800 nm region, three-photon absorption (3PA) (cross-section, σ 3 ∼10 −73 cm 6 s 2 ) in the 900–1200 nm region and four-photon absorption (4PA) (cross-section, σ 4 ∼10 −100 cm 8 s 3 ) in the 1300–1500 nm spectral region. These multi-photon absorption processes are explained using a simple band diagram. The measured NLO coefficients and cross-sections are fairly large when compared to some of the earlier reports on perovskite-based NCs. Cs4 PbBr6 0-D PRM also demonstrated a large third-order NLO susceptibility χ (3) (∼10 −7 esu), which can be attributed to the strong quantum confinement arising from spatially isolated, exciton containing individual [PbBr6 ] 4− octahedron. These results clearly suggest the potential of 0D-PRMs in applications such as photonics and ultrafast all-optical switching devices.